Synergistic induction of IL-23 by TNFα, IL-17A, and EGF in keratinocytes. (February 2021) - Ehst, Benjamin; Wang, Zhiping; Leitenberger, Justin; McClanahan, Danielle; De La Torre, Rachel; Sawka, Erika; Ortega-Loayza, Alex G.; Strunck, Jennifer; Greiling, Teri; Simpson, Eric; Liu, Yuangang
Highlights: IL-23 is induced by TNFα and IL-17A in keratinocytes. IL-23 induction by TNFα and IL-17A is enhanced in psoriatic keratinocytes. EGFR signaling is required for effective IL-23 induction by TNFα and IL-17A in keratinocytes. IL-23 induction by TNFα and IL-17A is specific to keratinocytes but not monocytes. Abstract: IL-23 is an inflammatory cytokine that plays an essential role in Th17 immunity by enhancing Th17 cell proliferation and survival, and Th17 cytokine production. IL-23 has pathogenic roles in the development of Th17-mediated inflammatory diseases including psoriasis. Despite successful treatment of psoriasis by blocking IL-23, the regulation of IL-23 expression in psoriasis patients is largely unknown. Dendritic cells are generally considered to be the primary source of IL-23 in psoriasis. While high levels of IL-23 are found in psoriatic epidermis, IL-23 expression in psoriatic keratinoctyes remains a controversial issue. In this study, we demonstrated that IL-23 production is induced by a combination of TNFα and IL-17A in human keratinocytes. Additionally, this IL-23 induction by TNFα and IL-17A is further increased in psoriatic keratinocytes and is enhanced by EGFR signaling. Although IL-23 is also robustly induced by toll-like receptor agonists in dendritic cells and macrophages, IL-23 expression in these cell types is not regulated by TNFα, IL-17A, and EGFR signaling. Given that IL-23 is essential for maintaining Th17 activation, IL-23 induction by TNFα, IL-17A, and EGF in keratinocytes could play an important pathological role in psoriasis pathogenesis as well as the cutaneous rash associated with EGFR inhibition therapy.